Managing Chiari I Malformations; 5 Year Experience - Sedain , G; Pradhanang, A; Sharma, MR; Shilpakar, SK (Journal of Institute of Medicine Nepal, 2024)
Introduction: Chiari I malformations present with variety of symptoms. There are four types of Chiari malformations described in literature. There are two more types of Chiari introduced later; Chiari 0 and Chiari 1.5. Routine use of MRI has led to frequent identification of the Chiari malformation. Management of Chiari malformation has evolved with time. Asymptomatic patients can be managed conservatively  with regular clinical and radiological follow up. Surgical management includes decompression of foramen magnum. This creates a space so that circulation of CSF is unimpeded. We analyzed patients who underwent surgical management at our centre in last 5 years.Methods: Retrospective analysis of all patients operated in Neurosurgery department of TUTH (Tribhuvan University Teaching Hospital) from 2012 July to 2017 July was done. Data was collected from hospital records and follow up was taken from outpatient department. Demography, associated syringomyelia, improvement in clinical symptoms and radiological improvement were analyzed. Minimum follow up of 1 year was included.Results: A total of 37 patients were available for analysis. Male to female ratio was 15:22. Major presentation was occipital headache sensory impairment and atrophy of upper limb due to syringomyelia. Clinical and radiological improvement was seen in all patients except 1 patient who developed post operative pneumonia and succumbed. Morbidity in the form of wound infection in 2, Pseudo meningocele was present in 4 patients and CSF leak in 3 patients. Resolution of syrinx was observed in 34 patients except in 3 patients who required a syringopleural shunt in follow up.Conclusion: Management of Chiari I malformation is relatively safe. In this era of diagnosis of more and more asymptomatic patients, clinical judgement is essential.